A rare compound heterozygosity of hemoglobin Siriraj and β-thalassemia in a 72-year-old male: A case report - Akella, Aparna; R, Shalini R; Bendre, Rajesh V. Bendre; Siddapuram, Siva prasad Siddapuram; Dodagatta-Marri, Eswari Dodagatta-Marri (Indian Journal of Case Reports, 2026)
Microcytic hypochromic Anemia in elderly patients is commonly attributed to iron deficiency or chronic disease. However, hemoglobinopathies may remain undiagnosed until late adulthood. A 72-year-old male with no significant clinical symptoms, with a history of hypertension, diabetes mellitus (type 2), and peripheral neuropathy, came to our Center for blood glucose levels. High-performance liquid chromatography (HPLC) revealed an abnormal hemoglobin (Hb) pattern with an HbC fraction of 74.6% and an elevated HbA2 of 8.9%. Subsequent molecular analysis using Sanger sequencing identified compound heterozygosity for Hb Siriraj and β-thalassemia. This case highlights the importance of considering rare Hb variants and molecular testing in elderly patients with unexplained microcytic anemia. The coexistence of Hb Siriraj and β-thalassemia is rare in the Indian population.